Decreased E‐Cadherin in MCF7 Human Breast Cancer Cells Forming Multicellular Spheroids Exposed to Simulated Microgravity. Issue 13 (19th June 2018) - Sahana, Jayashree; Nassef, Mohamed Zakaria; Wehland, Markus; Kopp, Sascha; Krüger, Marcus; Corydon, Thomas J.; Infanger, Manfred; Bauer, Johann; Grimm, Daniela
Abstract: MCF7 human breast cancer cells were cultured under normal gravity (1 g ) and on a random positioning machine (RPM) preventing sedimentation. After 2 weeks, adherent 1 g ‐control and adherent RPM cells (AD) as well as multicellular spheroids (MCS) were harvested. AD and MCS had been exposed to the RPM in the same culture flask. In a subsequent proteome analysis, the majority of the proteins detected showed similar label‐free quantification (LFQ) scores in each of the respective subpopulations, but in both AD or MCS cultures, proteins were also found whose LFQs deviated at least twofold from their counterparts in the 1 g ‐control cells. They included the cell junction protein E‐cadherin, which was diminished in MCS cells, where proteins of the E‐cadherin autodegradation pathway were enhanced and c‐Src (proto‐oncogene tyrosine‐protein kinase c‐Src) was detected. Spheroid formation was prevented by inhibition of c‐Src but promoted by antibodies blocking E‐cadherin activity. An interaction analysis of the detected proteins that are involved in forming and regulating junctions or adhesion complexes and in E‐cadherin autodegradation indicated connections between the two protein groups. This suggests that the balance of proteins that up‐ or downregulate E‐cadherin mediates the tendency of MCF7 cells to form MCS during RPM exposure.